Synthesis, Growth and Characterization of Nonlinear Optical Ce-Doped L-Prolinium Picrate Single Crystals - Gurumurthi, T.; Murugakoothan, P. (Asian Journal of Chemistry, 2014)
A non-linear optical material L-prolinium picrate and cerium doped L-prolinium picrate were synthesized and grown as single crystals by slow evaporation method. The grown crystals were subjected to structural, elemental, thermal, optical and dielectric studies. The structural analysis reveals that pure L-prolinium picrate and Ce doped L-prolinium picrate belongs to the monoclinic crystallographic system with space group P21. Optical transparency of the grown crystals was investigated by UV-visible-NIR spectrum. The thermal analyses reveal that Ce doped L-prolinium picrate is thermally stable up to 162 °C. The dielectric constant and dielectric loss of the crystals were studied as a function of frequency. The non-linear optical property of the doped crystal was confirmed by the Kurtz-powder second harmonic generation test and the result is compared with pure L-prolinium picrate. Mechanical strength of the crystals was also carried out by Vicker's micro hardness test.